Ocena jakości życia 8-letniego dziecka z obustronnym wrodzonym brakiem gałek ocznych - Średzińska-Kita, Dorota; Mrugacz, Małgorzata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Purpose: The main aim of our work was to estimate the physical and psychomotor development and the arrangement to the daily life for a 8 years old girl with inborn bilateral anophthalmia. Material and methods: The basic ophthalmic, pediatric and neurological examinations were performed with additional genetic and radiological examinations. Results: The ophthalmic and MRI examination find out the absence of the eyeballs, optic nerves, optic chiasm, optic tracts and optic radiation. Conclusions: Anophthalmia limits in a big grade an independent life of the child. However, currently the girl’s development indicates for good intellectual abilities what is promising for future independent life and professional work.